Cobalt selenide decorated polyaniline composite nanofibers as a newer counter electrode for dye‐sensitized solar cell. (16th April 2021) - Sowbakkiyavathi, Elindjeane Sheela; Murugadoss, Vignesh; Sittaramane, Ramadasse; Dhanusuraman, Ragupathy; Angaiah, Subramania
Abstract: The cobalt selenide nanoparticles (CoSe NPs) were prepared by a simple hydrothermal method, and polyaniline nanofibers (PANI NFs) were prepared by a chemical oxidative polymerization and its composite NFs were prepared by incorporating CoSe onto PANI at the optimized wt% 1:1 by ultrasonication to use as a newer photocathode for dye‐sensitized solar cells (DSSCs). The physio‐chemical properties of the prepared CoSe NPs/PANI NFs composite NFs were investigated by field emission scanning electron microscope, X‐ray diffractometer, and Raman spectroscopy. The results revealed that the phase pure CoSe NPs were decorated onto the PANI NFs without affecting their physio‐chemical nature. The electrochemical characteristics of CoSe NPs/PANI NFs composite NFs as photocathode were investigated by electrochemical AC‐impedance, cyclic voltammetry, and Tafel polarization studies. The CoSe decorated PANI composite NFs displayed excellent electrocatalytic behavior toward the tri‐iodide reduction. Further, DSSC fabricated with CoSe/PANI composite NFs as the photocathode exhibited the highest photoconversion efficiency of 9.14% than that of the pristine CoSe NPs and PANI NFs‐based counter electrodes (CEs). This is attributed to the synergistic electrocatalytic ability of CoSe NPs and the multiple interfacial charge transferability of PANI NFs. These results suggest that CoSe decorated PANI composite NFs could be used as a promising CE to fabricate high‐performance DSSC.